Computational investigation of heat transfer and pressure drop in a typical louver fin-and-tube heat exchanger for various louver angles and fin pitches - Okbaz, Abdulkerim; Olcay, Ali Bahad R.; Cellek, Mehmet Salih; Pinarbasi, Ali (E D P SCIENCES, 2017)
In this study 3-D numerical simulations on heat transfer and pressure drop characteristics for a typical louver fin-and-double-row tube heat exchanger were carried out. The heat transfer improvement and the corresponding pressure drop amounts were investigated depending on louver angles, fin pitch and Reynolds number, and reported in terms of Colburnj-factor and Fanning friction factor f. The heat transfer improvement and the corresponding pressure drop amounts were investigated depending on louver angles between 20 degrees <=theta <= 30 degrees, louver pitch of L-p=3.8 mm and frontal velocities of U between 1.22 m/s - 3 m/s. In addition, flow visualization of detailed flow features results, such as velocity vectors, streamlines and temperature counters have been shown to understand heat transfer enhancement mechanism. The present results indicated that louver angle and fin pitch noticeably affected the thermal and hydraulic performance of heat exchanger. It has been seen that increasing louver angle, increases thermal performance while decreasing hydraulic performance associated to pressure drop for fin pitches of 3.2 mm and 2.5 mm. Fin pitch determines the flow behaviour that for fin pitch of 2 mm, increasing louver angle decreased heat transfer and pressure drop. Velocity vectors and streamlines give considerable information about the flow whether it is duct directed or louver directed. For all conditions the flow is louver directed.
Keywords: PERFORMANCE; FLOW; Mechanics; Physics